UPDATED UZBEKISTAN, DEMOCRATIZATION OF SOCIETY AND INDIVIDUAL FREEDOM (Scientific journal of the Fergana State University, 2023)
The article is devoted to one of the topical issues of our time-the problems of democratization in the development of society. In this context, the main attention is paid to the issues of ensuring individual freedom in Uzbekistan and some controversial situations in this direction are highlighted.